Chinese business negotiations: South African firm experiences and perspectives - F. Horwitz; R. Hemmant; C. Rademeyer (South African Journal of Business Management, 2008)
South African business joint ventures in China are increasing. Successful negotiations are a key component when establishing a gateway into the Chinese market. This research is undertaken to establish South African business negotiators' understanding of Chinese business negotiation styles and behaviours and determinants of cross-cultural negotiation. Primary data was obtained through quantitative ranking style questionnaires and semi-structured interviews with selected South African business people who have had business negotiations with Chinese firms. The research revealed that perceptions held by South African business negotiators do not differ substantially from that of Westerners with regards to aspects such as trust relationships, hierarchical decision making, long-term decision making, networks and the concept of `face'.
Keywords: 650